Radiotherapy diagnostic biomarkers in radioresistant human H460 lung cancer stem-like cells. Issue 2 (1st February 2016) - Yun, Hong Shik; Baek, Jeong-Hwa; Yim, Ji-Hye; Um, Hong-Duck; Park, Jong Kuk; Song, Jie-Young; Park, In-Chul; Kim, Jae-Sung; Lee, Su-Jae; Lee, Chang-Woo; Hwang, Sang-Gu
ABSTRACT: Tumor cell radioresistance is a major contributor to radiotherapy failure, highlighting the importance of identifying predictive biomarkers for radioresistance. In this work, we established a radioresistant H460 (RR-H460) cell line from parental radiosensitive H460 lung cancer cells by exposure to fractionated radiation. The radiation-resistant, anti-apoptotic phenotype of RR-H460 cell lines was confirmed by their enhanced clonogenic survival and increased expression of the radioresistance genes Hsp90 and Her-3. RR-H460 cells displayed characteristics of cancer stem-like cells (CSCs), including induction of the surface marker CD44 and stem cell markers Nanog, Oct4, and Sox2. RR-H460 cells also exhibited sphere formation and malignant behavior, further supporting a CSC phenotype. Using proteomic analyses, we identified 8 proteins that were up-regulated in RR-H460 CSC lines and therefore potentially involved in radioresistance and CSC-related biological processes. Notably, 4 of these—PAI-2, NOMO2, KLC4, and PLOD3—have not been previously linked to radioresistance. Depletion of these individual genes sensitized RR-H460 cells to radiotoxicity and additively enhancing radiation-induced apoptosis. Our findings suggest the possibility of integrating molecular targeted therapy with radiotherapy as a strategy for resolving the radioresistance of lung tumors.